Sevoflurane–fentanyl versus propofol–fentanyl for tracheal intubation without neuromuscular blocking agents in elective surgery: A randomized controlled trial. (Student's Journal of Health Research Africa, 2026)
BackgroundObjectives: To compare sevoflurane–fentanyl versus propofol–fentanyl for tracheal intubation without a muscle relaxant and to assess intubating conditions, laryngoscopic view, apnea, and hemodynamic responses.MethodsThis prospective comparative observational study enrolled 80 ASA I–II adults over 18 months. After fentanyl 2 ug/kg, Group P received propofol 3 mg/kg IV with intubation at 90 seconds, while Group S underwent incremental sevoflurane induction up to 8% with intubation at 5 minutes. Intubating conditions were graded as optimal/good/poor/inadequate, Cormack–Lehane grade was recorded, and apnea was documented. Heart rate and blood pressure were recorded at baseline, after induction, after intubation, and at 1 and 5 minutes. Group comparisons used the t-test and chi-square.ResultsResults: Baseline characteristics were comparable between the two groups. Optimal intubating conditions were achieved more frequently with sevoflurane (92.5%) than with propofol (52.5%), while acceptable conditions were observed in 100% and 82.5% of patients, respectively. Apnea occurred in 12.5% of patients in the sevoflurane group compared with 100% in the propofol group. Laryngoscopic view was comparable between the groups. Heart rate and systolic blood pressure remained similar throughout the observation period. However, diastolic blood pressure and mean arterial pressure were significantly higher in the sevoflurane group at 1 and 5 minutes after intubation compared with the propofol group (p < 0.05), although the values remained within clinically acceptable limits in both groups.ConclusionSevoflurane–fentanyl provided superior intubating conditions with markedly lower apnea incidence and acceptable hemodynamic stability compared with propofol–fentanyl for tracheal intubation without neuromuscular blockade.RecommendationsIn ASA I–II elective cases where a muscle relaxant-free approach is planned, sevoflurane–fentanyl can be considered to optimize intubating conditions and reduce apnea, with continuous monitoring and readiness for rescue neuromuscular blockade.
Keywords: sevoflurane; propofol; fentanyl; tracheal intubation; muscle relaxant-free; elective surgery; hemodynamics